24.I. Workshop: Maximize impacts of research on public health policies: examples from the HBSC international study. (30th September 2020) - ,; ,
Abstract: Adolescence is a crucial and challenging transition between childhood and adulthood with its own specificities. A time when protective health behaviours and healthy lifestyles can be valued and adopted, or criticized and rejected, depending on complex interactions between contextual and individual factors. Even if overall adolescence can be seen as the period where individuals are the healthiest and the lowest users of health care. However, integration of young people's health in all policies and research agendas should remain of upmost importance, with a strong emphasis given to reducing social and health inequalities and inequities, in a broad public health perspective. In any case, public health policies targeting young people cannot be fully relevant and efficient if they do not rely on quality data collected among them, taking their voices into account as much as possible. Contrasted national examples will be shared to illustrate the benefits of linking scientific evidence to stakeholders' expectations, policy relevance, in a public health perspective. Since 1982 the Health behaviour in School-aged children (HBSC) survey collects data among 11, 13- and 15-year-old students, in a growing number of mostly European countries (50 in 2020), under the auspices of WHO. Every 4 years, through anonymous self-completed questionnaires filled in in class, using shared validated instruments and methods, new data is collected. This workshop aims at sharing contrasted national case studies (different countries -Ireland, France, Portugal, Poland, Lebanon- & different perspectives and topics: nutrition, tobacco-use, child participation, partnership) illustrating how data, collected among school-children can be used to inform and improve policies targeted at adolescents in the field of health, health behaviours well-being and their determinants, in partnership with different bodies and stakeholders. All presentations will rely on data collected through the HBSC survey, whose longevity, scope, expertise & reputation are unique in the field of adolescent health. Presenters belong to teams that have a longstanding experience of research on adolescents and in conducting the HBSC survey and share a strong interest in promoting the improvement of the health and well-being of the adolescents in their country, through interacting with various stakeholders including young people, teachers, principals, parents and policy makers. The presentations and debates will start from a common ground (HBSC), allowing for more time to be devoted on how to maximize the impact of research on Public health policies and the involvement of stakeholders in data valorization. Key messages: Research findings on adolescents' health and health behaviour can be shared with and used by stakeholders and be an asset for public health policies targeting young people. National case studies different in scopes & ambitions but relying on the same international project can be used to debate with other teams & countries around improving links between research & policy.